SALES FORECASTING FOR MIXUE ICE CREAM PRODUCTS USING THE TREND MOMENT METHOD - Tambunan, Fitra Dorica; Anita, Anita; Christin, Julia (JOISIE (Journal Of Information Systems And Informatics Engineering), 2025)
Sales of consumen products often experience fluctuations each period, so proper sales planning is required to ensure that the company’s operational activities run smoothly. The problem that arises is the absence of a forecasting model that is easy to use but capable of producing accurate results. This study aims to develop a sales forecasting model using the Trend Moment method. This method is chosen because it is simple and can be used to identify the direction of trends based on previous sales data. This study utilizes monthly sales data collected over a one-year period. The Trend Moment method in this study successfully achieved a MAPE value of 1.8% and an accuracy rate of 98.2%. These values indicate that the model is sufficiently accurate in forecasting sales. The results of this model can assist the company in planning production, managing distribution, and controlling inventory. This study is also beneficial as a basis for developing simple forecasting models for similar products in the future.